METHODOLOGICAL APPROACHES TO DANCE CULTURE STUDIES: THE NEED FOR DOCUMENTARY AND SOURCE-BASED PUBLISHING. A REVIEW OF HISTORICAL DANCE RESEARCH - Reglińska-Jemioł, Anna (Prace Polonistyczne, 2025)
In light of the growing appreciation of dance as a subject of scholarly research (in theatre studies, literary studies, cultural studies, anthropology), the key question is not merely the purpose, but the method of publishing source texts related to the history of dance. There are still very few publishing initiatives that emphasize and promote the concept of source material, which is so crucial in the humanities. Such initiatives would facilitate the reception and advancement of research into the dance culture of past eras (much like the established series, e.g., “Monumenta Musicae in Polonia” or “Theatroteka. Źródła i materiały do historii teatru”, have done for related fields). On the fringes of these considerations, particularly in ballet criticism and theatre studies, there is also a noticeable ambiguity (also in terms of genre classification) regarding the status of the ballet libretto. The evaluation, analysis, and interpretation of the libretto (also as a primary source of the performance) seem to rely on unclear criteria. Discussions on the state of research into dance literature and sources in Poland, as well as its future prospects, have been held in cultural studies for years (their analysis was already undertaken, among others, by Janina Pudełek in Pamiętnik Teatralny as early as 1965). More recently, in the 2022 issue of “Studia Choreologica” (vol. 23), Tomasz Nowak publish an article titled: “Polish Handwritten Collection of Ballets de Noverre – Present Status and Research Perspectives”. This serves as evidence of the ongoing focused scholarly inquiry into this problem.